DEVELOPMENT OF DIGITAL LITERACY AMONG STUDENTS AND POTENTIAL RISKS OF DIGITAL DEMENTIA - CHRÁSKA, Miroslav (Trends in education, 2015)
The paper describes the current concept of digital literacy among students and addresses the possible risks of so-called digital dementia.
Keywords: digital literacy; pupil; digital dementia; Facebook.